The restaurant of lost recipes ebook - Kashiwai, Hisashi (Kamogawa Food Detectives, 2024)
We all hold lost recipes in our hearts. A very special restaurant in Kyoto helps find them . . . Tucked away down a Kyoto backstreet lies the extraordinary Kamogawa Diner, run by Chef Nagare and his daughter, Koishi. The father-daughter duo have reinvented themselves as “food detectives,” offering a service that goes beyond cooking mouth-watering meals. Through their culinary sleuthing, they revive lost recipes and rekindle forgotten memories. From the Olympic swimmer who misses his estranged father’s bento lunchbox to the one-hit-wonder pop star who remembers the tempura she ate to celebrate her only successful record, each customer leaves the diner forever changed—though not always in the ways they expect . . . The Kamogawa Diner doesn’t just serve meals—it’s a door to the past through the miracle of delicious food. A beloved bestseller in Japan, The Restaurant of Lost Recipes is a tender and healing novel for fans of Before the Coffee Gets Cold .